Bioinformatics algorithms : design and implementation in Python - Rocha, Miguel P.; Ferreira, Pedro G. (Academic Press, an imprint of Elsevier, 2018)
'Bioinformatics Algorithms' provides a comprehensive book on many of the most important bioinformatics problems, putting forward the best algorithms and showing how to implement them. The book focuses on the use of the Python programming language and its algorithms, which is quickly becoming the most popular language in the bioinformatics field. Readers will find the tools they need to improve their knowledge and skills with regard to algorithm development and implementation, and will also uncover prototypes of bioinformatics applications that demonstrate the main principles underlying real world applications.